Specific Inhibitory Effect of κ-Carrageenan Polysaccharide on Swine Pandemic 2009 H1N1 Influenza Virus. - Qiang Shao; Qiang Guo; Wen ping Xu; Zandong Li; Tong tong Zhao (PLoS ONE, 2015)
The 2009 influenza A H1N1 pandemic placed unprecedented demands on antiviral drug resources and the vaccine industry. Carrageenan, an extractive of red algae, has been proven to inhibit infection and multiplication of various enveloped viruses. The aim of this study was to examine the ability of κ-carrageenan to inhibit swine pandemic 2009 H1N1 influenza virus to gain an understanding of antiviral ability of κ-carrageenan. It was here demonstrated that κ-carrageenan had no cytotoxicity at concentrations below 1000 μg/ml. Hemagglutination, 50% tissue culture infectious dose (TCID50) and cytopathic effect (CPE) inhibition assays showed that κ-carrageenan inhibited A/Swine/Shandong/731/2009 H1N1 (SW731) and A/California/04/2009 H1N1 (CA04) replication in a dose-dependent fashion. Mechanism studies show that the inhibition of SW731 multiplication and mRNA expression was maximized when κ-carrageenan was added before or during adsorption. The result of Hemagglutination inhibition assay indicate that κ-carrageenan specifically targeted HA of SW731 and CA04, both of which are pandemic H1N/2009 viruses, without effect on A/Pureto Rico/8/34 H1N1 (PR8), A/WSN/1933 H1N1 (WSN), A/Swine/Beijing/26/2008 H1N1 (SW26), A/Chicken/Shandong/LY/2008 H9N2 (LY08), and A/Chicken/Shandong/ZB/2007 H9N2 (ZB07) viruses. Immunofluorescence assay and Western blot showed that κ-carrageenan also inhibited SW731 protein expression after its internalization into cells. These results suggest that κ-carrageenan can significantly inhibit SW731 replication by interfering with a few replication steps in the SW731 life cycles, including adsorption, transcription, and viral protein expression, especially interactions between HA and cells. In this way, κ-carrageenan might be a suitable alternative approach to therapy meant to address anti-IAV, which contains an HA homologous to that of SW731.